2020
DOI: 10.1002/smll.202006255
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Pd Single Atoms, Clusters, and Oxygen Vacancies on TiO2 for Photocatalytic Hydrogen Evolution Coupled with Selective Organic Oxidation

Abstract: Developing efficient photocatalysts for synchronously producing H2 and high value‐added chemicals holds great promise to enhance solar energy conversion. Herein, a facile strategy of simultaneously engineering Pd cocatalyst and oxygen vacancies (VOs) on TiO2 to promote H2 production coupled with selective oxidation of benzylamine is demonstrated. The optimized PdSA+C/TiO2‐VO photocatalyst containing Pd single atoms (SAs), clusters (C), and VOs exhibits much superior performance to those of TiO2‐VO and PdSA/TiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(84 citation statements)
references
References 49 publications
0
84
0
Order By: Relevance
“…[ 26–28 ] Nevertheless, the high cost and low availability of the noble metals are the main inherent limitations for their various wide applications. [ 29,30 ] Thus, it is quite essential to explore alternative high‐efficiency H 2 ‐evolution cocatalyst with low cost and natural abundance for the achievement of clean and sustainable hydrogen energy.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26–28 ] Nevertheless, the high cost and low availability of the noble metals are the main inherent limitations for their various wide applications. [ 29,30 ] Thus, it is quite essential to explore alternative high‐efficiency H 2 ‐evolution cocatalyst with low cost and natural abundance for the achievement of clean and sustainable hydrogen energy.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of the photocatalytic HER activity of some typical precious metal-based SACs is listed in Table 2. 35,82,131,140,141,157,168,173,186,194,211,222,236,244,252,255,270,273,275,277,[291][292][293] Although the SA amounts in most of SACs were low, the selection of SA type displayed a crucial role in enhancing the photocatalytic activity of SACs. Compared with other precious SAs such as Au, Rh and Ag, Pt and Pd SAs exhibited far superior photocatalytic activity for the HER.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the defects of the substrates such as cation and anion vacancies play critical roles in determining the coordination environments and electronic structures of metal centers. 96,112,144,145,213,[244][245][246][247][248][249][250][251] More specically, substrates with vacancies can be used for effectively anchoring metal SAs in the preparation process due to the offered coupling sites. The vacancies on the support surface in SACs can avoid the aggregation of SAs, create strong interactions between SAs and the substrate and form metal-metal bonds to keep active metals atomically dispersed, signicantly improving the photocatalytic performance.…”
Section: Defect Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…In further, the origin of excellent photocatalytic HER activity of SACs has been studied widely. [47][48][49][50] The SACs usually own extremely high ratio of exposed atoms and high atomic utilization efficiency. The superior photocatalytic HER performance of Ag 1 /CN than Ag NPs/CN stem from more visible light absorbtion ability, suitable electronic structure and hydrogen and the high atomic utilization efficiency.…”
Section: Photocatalytic Her Performancementioning
confidence: 99%